The The Timun Mas Folktale as a Source of Inspiration for the Science Fiction Comic MOONA - Ziyad Fikrin Najib; Arif Fiyanto (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Folklore is a cultural heritage that preserves moral, ethical, and social values that remain relevant for adaptation into modern media. Timun Mas, one of the popular legends from Central Java, conveys messages of affection, courage, and wisdom, which hold strong potential for creative reinterpretation. However, interest in folklore among younger generations tends to decline due to the dominance of global popular culture. This study aims to explore the adaptation of the Timun Mas story into a science fiction comic entitled MOONA. The research method employed is a literature study on sources related to the Timun Mas narrative, comic theory, and similar adaptation works, followed by a creative process consisting of pre-production, production, and post-production stages. The final product is a 26-page comic that merges traditional elements with the science fiction genre, reconstructing the original characters and conflicts into a futuristic setting without losing its cultural values. This adaptation serves as an effort to preserve cultural heritage through visual media aligned with modern readers’ preferences, while also contributing to the growth of the local creative industry. The study demonstrates that folklore can be effectively developed through science fiction comics, providing a new form of cultural preservation and creative innovation.